Definition Diets and Deteriorating Masculinity? Bodybuilding Diets in Mid-Century America. Issue 1 (2nd January 2021) - Murtha, Ryan; Heffernan, Conor; Hunt, Thomas
ABSTRACT: In the late 1960s Steve Davis, a young strength athlete turned bodybuilder, prepared for an upcoming photoshoot by consuming nothing but meat and water. Far from unique, Davis represented a new line of bodybuilders who engaged in extreme dietary behaviors to achieve a lean and muscular look. Three decades prior to Davis' photoshoot, Dave Willoughby, an influential weightlifter and fitness writer, promoted a diet defined by its wholesome foods eaten in moderation. Comparing the contrasts between Davis and Willoughby's approaches, the following article sheds light on the still relatively unexplored area of bodybuilding diets in twentieth century America. Studying the shift in bodybuilding from health to purely aesthetic concerns, this article argues that food for the 1970s bodybuilder became a means self-fashioning. This change was driven by a conflux of competitive, chemical and societal factors. The article thus addresses the nexus between food, sport and gender in the United States